SCIENTIFIC AND LEGAL FACTS IN TAX LAW: THE RELATION CONCEPTs - Баїк, Оксана Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2019)
Purpose: analyze the relation between the concepts «scientific fact» and «legal fact». Methods: analysis, synthesis, induction, deduction, abstraction, concretization, generalization. Results: the author's conclusions about the similarity and difference between the concepts of «scientific fact» and «legal fact» in tax law, definition of their peculiarities. Discussion: general theoretical approaches to the understanding of the concepts of «scientific fact» and «legal fact» were clarified, which became the basis for explaining the essence of these concepts to tax law. The article analyzed the definition of the term «fact», which underlies the understanding of such concepts as «scientific fact» and «legal fact», as well as their features. It is noted that scientific facts are characterized by certain features that distinguish them from other types of facts. Concerning the scientific facts that take place in tax law, it is emphasized that the current tax law of Ukraine has its own conceptual and categorical apparatus. The scientific facts of tax law are based on the use of extensive methodological tools, use of available statistical data, comprehensive analysis of concepts, categories and terms of tax law, such as: tax relations, tax rules, legal facts, responsibility for violation of tax legislation of Ukraine, etc. It is noted that scientific facts do not need to be equated with legal facts. At the same time, it should be noted that the existence of legal facts in tax law contributes to a combination of objective and subjective features. The author concluded that in the tax law the basis of understanding of the concepts of «scientific fact» and «legal fact» is laid both general and industry approaches. Their common conceptual basis is to understand fact in meaning as what has already been done. It is a scientific fact that the scientific result (generalization) of the study of the object of tax and legal reality or phenomenon by means of certain means characteristic of science (statistical data, interviewing of the respondents, etc.) becomes duly recognized and recorded. Contrary to a scientific fact, a legal fact in tax law is generally considered to be circumstances or phenomena already provided for in tax law that affect the occurrence, alteration or termination of a tax relationship. That is, a scientific fact needs to be asserted as having occurred before it is recognized as scientific. It is concluded that the tax law is based on the understanding of the concepts of «scientific fact» and «legal fact» laid both general and industry approaches.